Dual Activation of Molecular Oxygen and Surface Lattice Oxygen in Single Atom Cu1/TiO2 Catalyst for CO Oxidation. (25th October 2022) - Fang, Yarong; Zhang, Qi; Zhang, Huan; Li, Xiaomin; Chen, Wei; Xu, Jue; Shen, Huan; Yang, Ji; Pan, Chuanqi; Zhu, Yuhua; Wang, Jinlong; Luo, Zhu; et al.
Abstract: The in‐depth mechanism on the simultaneous activation of O2 and surface lattice O 2− on one active metallic site has not been elucidated yet. Herein, we report a strategy for the construction of abundant oxygen activation sites by rational design of Cu1 /TiO2 single atom catalysts (SACs). The charge transfer between isolated Cu and TiO2 support generates abundant Cu I and 2‐coordinated Olat sites in Cu1 −O−Ti hybridization structure, which facilitates the chemisorption and activation of O2 molecules. Simultaneously, the Cu1 −O−Ti induced TiO2 lattice distortion activate the adjacent surface lattice O 2−, achieving the dual activation of O2 and surface lattice O 2− . The Cu1 −O−Ti active site switches the CO oxidation mechanism from Eley‐Rideal (80 °C) to Mars–van Krevelen route (200 °C) with the increase of reaction temperature. The dual activation of O2 and surface lattice O 2− can by modulating the electron properties of SACs can boost the heterogeneous catalytic oxidation activity. Abstract : The isolated Cu 1+ on Cu1 /TiO2 single atom catalysts (SACs) facilitated the simultaneous activation of chemisorbed O2 and 2‐coordinated surface lattice O 2−, which triggered the CO oxidation through E‐R (80 °C) and MvK (200 °C) routes synergistically with elevated temperature. This finding provides insights and strategy for the rational design of efficient oxidation catalysts with sufficient reactive oxygen species for practical application.